(untitled) (Journal of the College of Basic Education, 2024)
The research aims to know the effect of Micro Teaching on learning scouting skills, and to identify the preference between the experimental and control research groups. The experimental method was used because it suits the nature of the research. The research was conducted on third-year students in the Department of Physical Education and Sports Sciences/College of Basic Education for the academic year (2023-2024) as The research sample consisted of (59) male and female students, divided into five study groups: (A-B). The research sample was chosen randomly (by lottery) from the original population. They represented the two groups (A and B), respectively, and were divided into two experimental groups. And a control group with (15) students for the experimental group taught according to ( Micro Teaching ) and (15) students for the control group taught according to (the traditional method) Teaching units on learning scouting skills have been prepared in the second semester of the year (2023-2024), taught in light of the content of the prescribed curriculum. The program took (6) weeks to implement, with one educational unit per week. After completion of its implementation, post-tests were conducted, data was collected and processed using appropriate statistical methods, and the following conclusions were reached: 1- The exercises according to the Micro Teaching had a clear and effective impact in developing the students’ ability to learn skills. 2- The Micro Teaching students to interact, participate, work in groups, and ask a number of questions that develop their ideas and encourage them to solve the problems they face